KEMAMPUAN ARTIFICIAL INTELLIGENCE TERHADAP PENDETEKSIAN FRAUD: STUDI LITERATUR - Mawlidy, Ervian Ridho; Dio, Rieswandha; Lorensa, Like (Faculty of Economics and Business University of Mataram, 2024)
This study aims to determine the role of Artificial Intelligence (AI) in detecting financial fraud in audits. As auditors increasingly rely on AI technology to process large amounts of data, ensuring the confidentiality and integrity of that data is critical. The research was conducted by collecting 16 articles from reputable journals published in 2018–2024. The categorization was determined by the methodologies employed, and the findings yielded A systematic literature review (SLR) that scrutinizes various aspects of published articles, including their results, methodologies, subject matters, recommendations, and constraints. The findings offer substantiated evidence supporting the beneficial role of artificial intelligence (AI) in detecting financial fraud during audits. The forms of AI that have been implemented in companies are artificial neural networks (ANN) and machine learning. Privacy concerns, data security, and ethical considerations around the use of sensitive information are essential factors that must be addressed.